Cognitive–behavioural therapy combined with music therapy for chronic fatigue following Epstein-Barr virus infection in adolescents: a feasibility study. Issue 1 (9th April 2020) - Malik, Sadaf; Asprusten, Tarjei Tørre; Pedersen, Maria; Mangersnes, Julie; Trondalen, Gro; van Roy, Betty; Skovlund, Eva; Wyller, Vegard Bruun
Abstract : ​Background: Cognitive–behavioural therapy (CBT) is effective in chronic fatigue syndrome. However, CBT has not been investigated in postinfectious chronic fatigue (CF), nor is it known whether addition of therapeutic elements from other disciplines might be feasible. We studied the feasibility of a combined CBT and music therapy intervention for CF following Epstein-Barr virus (EBV) infection in adolescents. ​Methods: Adolescents (12–20 years old) participating in a postinfectious cohort study who developed CF 6 months after an acute EBV infection were eligible for the present feasibility study. A combined CBT and music therapy programme (10 therapy sessions and related homework) was compared with care as usual in a randomised controlled design. Therapists and participants were blinded to outcome evaluation. Endpoints included physical activity (steps/day), symptom scores, recovery rate and possible harmful effects, but the study was underpowered regarding efficacy. Total follow-up time was 15 months. ​Results: A total of 43 individuals with postinfectious CF were included (21 intervention group, 22 control group). Seven individuals left the study during the first 3 months, leaving 15 in the intervention group and 21 in the control group at 3 months' follow-up. No harmful effects were recorded, and compliance with appointment was high. In intention-to-treat analyses, number of steps/day tended to decrease (difference=−1158, 95% CI −2642 to 325), whereas postexertional malaise tended to improve (difference=−0.4, 95% CI −0.9 to 0.1) in the intervention group at 3 months. At 15 months' follow-up, there was a trend towards higher recovery rate in the intervention group (62% vs 37%). ​Conclusion: An intervention study of combined CBT and music therapy in postinfectious CF is feasible, and appears acceptable to the participants. The tendencies towards positive effects on patients' symptoms and recovery might justify a full-scale clinical trial. ​Trial registration number: NCT02499302 .